The Influence of Student Discipline and Learning Facilities on the Motivation of State Elementary School Teachers - Alfiansyah Alfiansyah; Yasir Arafat; Nuril Furkan (Journal of Social Work and Science Education, 2026)
This study aims to identify and describe the combined influence of student discipline and learning facilities on teachers’ motivation in public elementary schools in Sako District, Palembang, Indonesia. Employing a descriptive quantitative method, the research was conducted across 10 schools over six months (June-November 2025). The population comprised 225 teachers (civil servants, contract, and honorary staff), with a sample of 69 respondents determined through appropriate calculations. Data collection utilized questionnaires, observations, and documentation, while analysis involved normality, linearity, and multicollinearity tests, alongside simple and multiple correlation analysis, regression analysis, t-tests, and F-tests. The findings reveal a significant combined influence of student discipline and learning facilities on teacher motivation. Notably, the magnitude of this combined influence contributes 99.2% to teachers’ motivation, indicating an exceptionally strong predictive relationship. The novelty of this study lies in its quantitative demonstration of the near-total combined effect of these two specific school environment factors on teacher motivation within the Indonesian elementary school context, moving beyond isolated examinations of each variable. Practically, these findings underscore for school administrators and policymakers the critical importance of simultaneously fostering student discipline and improving learning facilities as dual strategies to enhance teacher motivation. This study contributes to educational management literature by providing robust empirical evidence on the synergistic impact of student behavior and physical resources on teacher morale, highlighting their interdependence in shaping a motivating work environment.